Human odontoblast-like cells produce nitric oxide with antibacterial activity upon TLR2 activation - FARGES, Jean-Christophe; Bellanger, Aurélie; Ducret, Maxime; Aubert-Foucher, Elisabeth; Richard, Beatrice; Alliot-licht, Brigitte; Bleicher, Françoise; Carrouel, Florence (Frontiers in Physiology, 2015)
The penetration of cariogenic oral bacteria into enamel and dentin during the caries process triggers an immune/inflammatory response in the underlying pulp tissue, the reduction of which is considered a prerequisite to dentinogenesis-based pulp regeneration. If the role of odontoblasts in dentin formation is well known, their involvement in the antibacterial response of the dental pulp to cariogenic microorganisms has yet to be elucidated. Our aim here was to determine if odontoblasts produce nitric oxide (NO) with antibacterial activity upon activation of Toll-like receptor-2 (TLR2), a cell membrane receptor involved in the recognition of cariogenic Gram-positive bacteria. Human odontoblast-like cells differentiated from dental pulp explants were stimulated with the TLR2 synthetic agonist Pam2CSK4. We found that NOS1, NOS2 and NOS3 gene expression was increased in Pam2CSK4-stimulated odontoblast-like cells compared to unstimulated ones. NOS2 was the most up-regulated gene. NOS1 and NOS3 proteins were not detected in Pam2CSK4-stimulated or control cultures. NOS2 protein synthesis, NOS activity and NO extracellular release were all augmented in stimulated samples. Pam2CSK4-stimulated cell supernatants reduced Streptococcus mutans growth, an effect counteracted by the NOS inhibitor L-NAME. In vivo, the NOS2 gene was up-regulated in the inflamed pulp of carious teeth compared with healthy ones. NOS2 protein was immunolocalized in odontoblasts situated beneath the caries lesion but not in pulp cells from healthy teeth. These results suggest that odontoblasts may participate to the antimicrobial pulp response to dentin-invading Gram-positive bacteria through NOS2-mediated NO production. They might in this manner pave the way for accurate dental pulp healing and regeneration.